An Effectiveness Evaluation on Critical Thinking Exercises in Chinese College English Textbooks - lyu, hui (Pacific International Journal, 2024)
Cultivating students’ critical thinking has long been the consensus reached by the international education circle and a common goal of international higher education reform. However, the training of critical thinking of college students in China started late, and no mature talent training system has been formed in higher education. As a compulsory public basic course for college students in China, College English is one of the most involved courses in universities. As an important material and tool for teaching and learning, the design quality of college English textbook exercises will directly affect the quality of teaching and talent training. Therefore, this study analyzes the effectiveness of textbook exercise design, with a view to contributing to college English textbooks and teaching reform, so as to help students develop critical thinking. In this study, exercises in New Horizons College English (Reading and Writing Course 1), one of the most widely used textbooks, were selected for discourse analysis, and the Delphi Panel’s Dualistic Model was used as a comparison for internal evaluation. Moreover, taking a Chinese university as an example, questionnaire survey are used to conduct external evaluation of textbook exercise design, found that: (a) Exercises in Chinese college English textbooks correspond to the cognitive skills mentioned in the Dualistic Model, which is helpful to the training of students' critical thinking; (b) There are also some problems, such as the imbalance of skills training and the homogenization of questioning methods; (c) Students of College English generally have a high recognition of the importance of critical thinking and textbook design, but believe that textbook design, course teaching and assessment need to be reformed.